Respuesta :

Answer:

f(x) - x = 2

Step-by-step explanation:

[tex]f(x)-x\\\\=\dfrac{7x+1}{3}-\dfrac{4x-5}{3}-x\\\\=\dfrac{7x+1}{3}-\dfrac{4x-5}{3}-\dfrac{3x}{3}[/tex]

[tex]=\dfrac{(7x+1)-(4x-5)-3x}{3}\\\\=\dfrac{7x+1-4x+5-3x}{3}\\\\=\dfrac{6}{3}\\\\=2[/tex]

Answer:

[tex]-\frac{4}{3}[/tex] or [tex]-1\frac{1}{3}[/tex]

Step-by-step explanation:

I could be 100% wrong ( I solved the problem the way it looks like it should be, but I don't recognize this way of writing one of these) but here we go:

[tex]f(x)=\frac{7x+1}{3}-\frac{4x-5}{3} \\f(x)-x=\frac{7x+1}{3}-\frac{4x-5}{3}-x \\=\frac{7x+1}{3}+\frac{-4x+5}{3}-x \\=\frac{3x-6}{3}-\frac{3x}{3}\\ =-\frac{6}{3}=-2[/tex]

A little explanation:

Consider that f(x) is equal to what they tell you it is. With that in mind, f(x)-x would most likely be what they told you f(x) was with a "-x" slapped onto it.

Also:

[tex]\frac{3x}{3}=x[/tex] because any number divided by itself is one so 3/3=1 and 3x/3=1x=x

Hope I could help :)